Development of a Technique for Generating Unique Land Use Maps Using Remote Sensing Information - Kayumov Odiljon Abduraufovich (Zien Journals, 2023)
Land use maps play a crucial role in environmental management, natural resource conservation, and urban planning. Remote sensing technology has emerged as a powerful tool for mapping land use, with high accuracy and low cost. This article presents a new method for creating special land use maps using remote sensing data. The method involves the integration of multiple remote sensing datasets, such as satellite images, aerial photographs, LiDAR data and the application of machine learning algorithms, such as Random Forest and Support Vector Machine. The result is a comprehensive and accurate land use map that can be used for a wide range of applications
Keywords: Remote sensing; Land use; Mapping; Machine learning